Sigmodontinae rodents as hosts for larvae and nymphs of Ixodes loricatus Neumann, 1899 (Acari: Ixodidae) - Nava, Santiago (2004)
Larvae and nymphs of Ixodes loricatus Neumann, 1899 ticks (confirmed by morphological characters and by comparison of 16S mitochondrial rDNA sequences) were collected from Sigmodontinae Wagner, rodents in central and northern Argentina and Uruguay. A total of 100 larvae and 38 nymphs of I. loricatus were collected on the genera Akodon Meyen (n = 36 individuals), Calomys Waterhouse (n = 2), Oligoryzomys Bang (n = 12), Oxymycterus Waterhouse (n = 9), and Scapteromys Waterhouse (n = 13). 72 larvae and 18 nymphs were collected on Akodon. Adults of I. loricatus were found in central Argentina and Uruguay on Didelphimorphia of the genera Didelphis Linnaeus and Lutreolina Thomas. Ixodes loricatus has been considered a species with strict total specificity to Didelphimorphia. Our results show that this statement may not be justified. Sigmodontinae rodents are sympatric and share habitats with the phylogenetically distant Didelphimorphia; infestation with I. loricatus seems to be its consequence. We tentatively consider I. loricatus moderately specific to Didelphimorphia.